Recombination in Positive-Strand RNA Viruses - Wang, Haiwei; Cui, Xingyang; Cai, Xuehui; An, Tongqing (Frontiers in Microbiology, 2022)
RNA recombination is a major driver of genetic shifts tightly linked to the evolution of RNA viruses. Genomic recombination contributes substantially to the emergence of new viral lineages, expansion in host tropism, adaptations to new environments, and virulence and pathogenesis. Here, we review some of the recent progress that has advanced our understanding of recombination in positive-strand RNA viruses, including recombination triggers and the mechanisms behind them. The study of RNA recombination aids in predicting the probability and outcome of viral recombination events, and in the design of viruses with reduced recombination frequency as candidates for the development of live attenuated vaccines. Surveillance of viral recombination should remain a priority in the detection of emergent viral strains, a goal that can only be accomplished by expanding our understanding of how these events are triggered and regulated.